Subjek Hukum Investasi Internasional dalam Forum ICSID: Teori dan Praktiknya - M. Azka Haiban (LPPM Universitas Ekasakti Padang, 2023)
Foreign Direct Investment (FDI) is essential in a globally integrated economic system when the host country needs the resources necessary for the development of its country's economy. However, differences in nationality make foreign investors vulnerable to host country government interference in their businesses. The inability of investors to participate in the democratic process in host countries makes International Investment Agreements (IIAs) and Bilateral Investment Treaties (BITs) important as a basis for providing substantive protection for investors. ICSID is a forum often referred to by investors in defending their rights and fulfilling their interests, as well as providing a dispute resolution system that allows every foreign investor to file a lawsuit against the host state government as the ICSID Convention regulates this. The results of the analysis show that the interpretation of subjects that can be disputed in ICSID can refer to Article 25(1) of the ICSID Convention. However, in practice, differences in tribunal interpretation in deciding which party can proceed and fulfill the dispute resolution criteria in the ICSID forum differ in several cases. In the case of East Kalimantan Regional Government vs PT Kaltim Prima Coal, the tribunal decided that the East Kalimantan Regional Government had stepped into the shoes of the State based on Article 25 (3) of the ICSID Convention. On the other hand, the acceptance of the Oleovest lawsuit by ICSID shows that non-state legal entities, in this context, multinational corporations, have the legitimacy to become parties to international investment disputes in several dispute resolution forums, such as ICSID, as long as there is relevance or relationship between the plaintiff and the BIT which is the basis of the activity. foreign investment or foreign investment in the host country.